Impact factors of Arctic research stations on the mental health of team members - Li, Huibao; Zou, Guangtian (Frontiers in Psychology, 2025)
IntroductionThe extreme, closed, and isolated environments of Arctic research stations have resulted in substantial challenges in the daily life and work of polar science expedition team members, often leading to various mental health problems. The mental health of the Arctic team members is related to the restorative quality of the station environment, which is primarily influenced by design factors. However, previous studies have mainly discussed these factors separately using a single approach, rarely providing comprehensive understanding into team members' perceptions of the station environment in an integrated manner.MethodsThis study uses a combination of qualitative and quantitative methods to determine the design factors and dimensions that affect the restorative potential of Arctic research stations, filling the gap in the design weight of restorative potential factors. First, environmental factors related to the mental health of team members in Arctic research stations were gradually screened through a literature review and semi-structured interviews. Then, questionnaire was used to collect the perspectives of 63 Chinese scientific research team members. Correlation analysis, principal component analysis, and statistical weight calculation were applied to the responses to investigate the restorative quality of design characteristics within a framework.ResultsThe findings showed that 24 design factors were associated with a restorative scientific research station environment. Among them, privacy of space was the most significant factor that could influence psychological recovery. Five primary components were identified: indoor conditions, configuration of space, physical environment, spatial perception, and space safety. Additionally, nine secondary components were identified: appearance design, spatial scale, interior facilities, space function, outdoor environmental influences, room adjustments, personal contact, interaction, and space safety. The weight calculation shows that indoor conditions and space configuration are the most significant dimensions that influence the restorative quality.DiscussionThis study provides a targeted analysis of the environmental factors and key dimensions of Arctic research stations, offering a theoretical basis and practical suggestions for architectural design of Arctic research stations that are more suitable for team members.